Dinamika Aktor dalam Formulasi Kebijakan Peraturan Daerah Kota Denpasar Nomor 3 Tahun 2020 Tentang Pengarusutamaan Gender - Artha Risma, Putu Natasya; Apriani, Kadek Dwita; Radita, Ni Wayan (Jurnal Nawala Politika; Vol 1 No 1 (2022): Jurnal Ilmu Politik 2022, 2022)
This study aims to determine the dynamics of actors in the formulation of Denpasar City Regulation Number 3 of 2020 concerning Gender Mainstreaming. The theory of policy design by Schneider and Ingram is used for analysis the dynamics actors during the formulation of Gender Mainstreaming policies in the parliament. In addition, the political theory of presence is also used for analysis the existence of women in the substance of the policy. By using qualitative methods through interviews, the results of the research are as follows: First, the dynamics of actors in the formulation of Gender Mainstreaming policies can be seen when determining the percentage substance in Article 15 Section 2. Second, the resulting Gender Mainstreaming policy is a sub-optimal policy because the resulting policy is administrative and technocratic. Third, gender mainstreaming policy formulation stops at the level of framing dynamics and at the level of descriptive presence.